To determine which equation has exactly the same solutions as \((x−7)(x+9)=0\), we first find the solutions of the original equation.
The equation \((x−7)(x+9)=0\) implies:
- \(x - 7 = 0\) → \(x = 7\)
- \(x + 9 = 0\) → \(x = -9\)
So, the solutions are \(x = 7\) and \(x = -9\).
Next, we will analyze each of the given equations to see if they produce the same solutions:
-
\(x^2 - 2x - 63 = 0\)
We can factor this equation or use the quadratic formula: \[ x^2 - 2x - 63 = (x-9)(x+7) = 0 \] The solutions are \(x = 9\) and \(x = -7\) (not the same as \(x = 7\) and \(x = -9\)). -
\(x^2 = 2x - 63\)
Rearranging gives: \[ x^2 - 2x + 63 = 0 \] Using the quadratic formula: \[ x = \frac{2 \pm \sqrt{(-2)^2 - 4 \cdot 1 \cdot 63}}{2 \cdot 1} = \frac{2 \pm \sqrt{4 - 252}}{2} = \frac{2 \pm \sqrt{-248}}{2} \] This will yield complex solutions (not the same). -
\(x^2 = -2x + 63\)
Rearranging gives: \[ x^2 + 2x - 63 = 0 \] Factoring or using the quadratic formula: \[ x^2 + 2x - 63 = (x - 7)(x + 9) = 0 \] The solutions are \(x = 7\) and \(x = -9\) (which are exactly the same as the original equation). -
\(x^2 + 2x = -63\)
Rearranging gives: \[ x^2 + 2x + 63 = 0 \] This will also yield complex solutions (not the same).
The correct option that has the same solutions as \((x−7)(x+9)=0\) is:
\(x^2 = -2x + 63\).